Isothermal crystallization and melting behavior of polypropylene/layered double hydroxide nanocomposites - Lonkar, Sunil P.; Singh, R. P. (Thermochimica Acta, 2009)
The effect of layered double hydroxide (LDH) nanolayers on the crystallization behavior of polypropylene (PP) was studied based on the preparation of nanocomposites by a melt intercalation method. The isothermal crystallization kinetics and subsequent melting behavior of PP/LDH hybrids were studied with differential scanning calorimetry (DSC), polarized optical microscopy (POM), and wide-angle X-ray diffraction (WAXD). Studies revealed that the LDH promoted heterogeneous nucleation, accelerating the crystallization of PR The Avrami equation successfully describes the isothermal crystallization kinetics of PP/LDH hybrids and signifies heterogeneous nucleation in crystal growth of PR The varying values of Avrami exponent (n) and half crystallization time (t(1/2)) of PP and PP/LDH hybrids describes overall crystallization behavior. The crystallite size (D(hkl)) and distribution of different crystallites in PP varied in presence of LDH. A significant increase in melting temperature is observed for PP/LDH hybrids. The POM showed that smaller and less perfect crystals were formed in nanocomposites because of molecular interaction between PP chains and LDH. The value of fold surface free energy (sigma(e)) of PP chains decreased with increasing LDH content. Finally, the overall results signify that LDH at nanometer level acted as nucleating agent and accelerate the overall crystallization process of PR (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Isothermal crystallization; Layered double hydroxide; Melting behavior; Polypropylene nanocomposites

Polypropylene-organoclay nanocomposites containing nucleating agents - Ghugare, S. V.; Govindaiah, P.; Avadhani, C. V. (Polymer Bulletin, 2009)
Polypropylene/organoclay nanocomposites containing nucleating agents, viz., aluminum hydroxybis[2,2-methylenebis(4,6-di-tert-butylphenyl) phosphate (NA21) and 1,3:2,4-bis(3,4-dimethylbenzylidene)sorbitol (Millad 3988), were prepared by direct melt intercalation in a twin-screw extruder. Nucleating agents were added to polypropylene during compounding and their effect on the properties of the nanocomposites was studied. X-ray diffraction (XRD) and transmission electron microscopy (TEM) exhibited clay layers to be intercalated and partially exfoliated. The expansion of inter-gallery distance of the clay layers was governed by the interaction between polypropylene, compatibilizer, and different nucleating agents. Thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC) indicated higher thermal stability and crystallization temperature for nanocomposites compared to virgin polymer. Even a small addition of the nanoscale filler with 0.2% nucleating agents was found to promote concurrently several PP material properties, including improved tensile characteristics, higher Young's modulus, increased thermal stability and rate of crystallization.
Keywords: Nucleating agents; organoclay; Polypropylene nanocomposites; Thermogravimetric analysis; transmission electron microscopy

Preparation and nonisothermal crystallization behavior of polypropylene/layered double hydroxide nanocomposites - Lonkar, Sunil P.; Morlat-Therias, Sandrine; Caperaa, N.; Leroux, Fabrice; Gardette, Jean Luc; Singh, R. P. (Polymer, 2009)
Polypropylene (PP)/layered double hydroxide (LDH) nanocomposites were prepared via melt intercalation using dodecyl sulfate anion modified LDH and maleated PP as compatibilizing agent. Evidently the interlayer anions in LDH galleries react with maleic anhydride groups of PP-g-MA and lead to a finer dispersion of individual LDH layers in the PP matrix. The nanostructure was characterized by XRD and TEM; the examinations confirmed the nanocomposite formation with exfoliated/intercalated layered double hydroxides well distributed in the PP matrix. The nonisothermal crystallization behavior of resulting nanocomposites was extensively studied using differential scanning calorimetry (DSC) technique at various cooling rates. In nonisothermal crystallization kinetics, the Ozawa approach failed to describe the crystallization behavior of nanocomposites, whereas the Avrami analysis and Jeziorny method well define the crystallization behavior of PP/LDH nanocomposite. Combined Avrami and Ozawa analysis (Liu model) also found useful. The results revealed that very small amounts of LDH (1%) could accelerate the crystallization process relative to the pure PP and increase in the crystallization rates was attributed to the nucleating effect of the nanoparticles. Polarized optical microscopy (POM) observations also support the DSC results. The effective crystallization activation energy was estimated as a function of the relative degree of crystallinity using the isoconversional analysis. Overall, results indicated that the LDH particles in nanometer size might act as nucleating agent and distinctly change the type of nucleation, growth and geometry of PP crystals. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Layered double hydroxide; Nonisothermal crystallization kinetics; Polypropylene nanocomposites